A chromatographic study on the retention behavior of the amylose tris(3‐chloro‐5‐methylphenylcarbamate) chiral stationary phase under aqueous conditions. Issue 21 (1st October 2018) - Cirilli, Roberto; Carradori, Simone; Casulli, Adriano; Pierini, Marco
Abstract: In this study, the retention properties of the immobilized polysaccharide‐derived Chiralpak IG‐3 chiral stationary phase under aqueous‐organic conditions were investigated. A systematic evaluation of the retention factors of the enantiomers of the chiral sulfoxide oxfendazole, endowed with anthelmintic activity and selected as test compound, was carried out changing progressively the water content in hydro‐organic eluents containing methanol, ethanol or acetonitrile. From the results obtained with acetonitrile/water mobile phases and the associated retention plots, clear U‐shape retention dependencies, indicative of the interplay of both hydrophilic interaction liquid chromatography and reversed‐phase modes, were highlighted. A U‐turn point of retention mechanism was recorded in correspondence of the acetonitrile/water 100:40 v/v mobile phase. Retention was significantly affected by small percentages of trifluoroacetic acid or diethylamine additives incorporated in the mobile phase. It is worth emphasizing that the basic additive was more effective in reducing retention in the reversed‐phase region, while the action of acid additive was more pronounced in the hydrophilic interaction liquid chromatography region. Finally, either in the transition from hydrophilic interaction liquid chromatography to reversed‐phase conditions or after additive addition, the enantioselectivity did not vary significantly.